POTENSI TUMBUHAN BAWAH PADA TEGAKAN HUTAN TANAMAN Acacia crassicarpa A. Cunn. ex Benth SEBAGAI PAKAN GAJAH DAN PENYIMPAN KARBON DI KABUPATEN OGAN KOMERING ILIR (The Potential of Understorey in Acacia crassicarpa A. Cunn. ex Benth Plantation for Elephant Feed and Carbon Storage in Ogan Komering Ilir Regency) - R Garsetiasih; Anita Rianti; Nur Muhammad Heriyanto (Jurnal Penelitian Hutan Tanaman, 2018)
ABSTRACT Understorey in a forest area can be utilized as herbivorous animal feed, as well as carbon storage. In Ogan Komering Ilir (OKI) Regency, the understorey is utilized by elephant as feed habitat. The study aimed to determine the diversity, productivity and potential for carbon content of understorey in A. Crassicarpa plantation in OKI Regency. The method used for collection of understorey data was square plot method with 1x1m size, where the first plot was determined randomly and followed by the subsequent plots systematically. The results found out 8 types of understorey species with important index values in sequence were Nephrolepis biserrata (Sw) Schott. 66.90%; Melastoma malabathricum L. 44.14% and Stenochlaena palustris (Burm. F.) Bedd. 36.18%. The species of feed that most eaten by the elephants were Nephrolepis biserrata (Sw.) Schott., Cyperus kyllinga Endl. and Stenochlaena palustris (Burm. f.) Bedd. The domination of understorey in the stand of Germplasm Conservation Area (KPPN) (0,1611) was greater compared to those in block A (0,1124) and block E (0,1512). The total biomass of the understorey in Block A (3 year old A. Crassicarpa stand), E Block (3,3 year old A. Crassicarpa stand), and KPPN were 561,8 kg/ha; 371,48 kg/ha; and 383,84 kg/ha, respectively. Carrying capacity of the understorey as feed for elephants during the dry season in block A was for 10,54 elephants; block E was for 2,10 elephants and KPPN was for 79,37 elephants. Therefore, in order to meet the requirement of elephant feed and minimize elephant interference to plantation, the quality of KPPN needs to be improved. Key word : Acacia crassicarpa, carbon, diversity, productivity, undergrowth  ABSTRAK Tumbuhan bawah hutan selain berfungsi sebagai pakan satwa herbivora juga dapat menyimpan karbon. Tumbuhan bawah pada tegakan Acacia crassicarpa di Kabupaten Ogan Komering Ilir juga dimanfaatkan oleh gajah sebagai habitat pakan. Tujuan penelitian adalah untuk mengetahui keanekaragaman dan produktivitas tumbuhan bawah serta potensi kandungan karbonnya. Pengumpulan data tumbuhan bawah menggunakan metode plot bujur sangkar berukuran 1 m x 1 m, penentuan plot pertama dilakukan secara acak dan selanjutnya secara sistematik. Hasil penelitian dijumpai delapan jenis tumbuhan bawah dengan nilai indeks penting secara berurutan yaitu paku harupat (Nephrolepis biserrata) sebesar 66,90%, harendong (Melastoma malabathricum) 44,14% dan jenis paku udang (Stenochlaena palustris) 36,18%. Penguasaan jenis tumbuhan bawah pada tegakan Kawasan Pelestarian Plasma Nutfah (KPPN) lebih besar (0,1611) dibandingkan pada tegakan di blok A dan blok E (0,1124 dan 0,1512). Biomassa tumbuhan bawah di blok A (tegakan A. crassicarpa 3 tahun), blok E (tegakan A. crassicarpa 3,3 tahun) dan Kawasan Pelestarian Plasma Nutfah (KPPN) berturut-turut adalah 561,8 kg/ha; 371,48 kg/ha; dan 383,84 kg/ha. Daya dukung tumbuhan bawah sebagai pakan gajah pada saat musim kemarau di blok A adalah 10,54 gajah; blok E sebesar 2,10 ekor gajah dan areal KPPN sebesar 79,37 gajah. Untuk memenuhi kebutuhan pakan gajah serta meminimalisir gangguan gajah terhadap hutan tanaman perlu peningkatan kualitas KPPN.Kata kunci : Acacia crassicarpa, karbon, keanekaragaman, produktivitas, tumbuhan bawah